Amphibian decline in a Central European forest and the importance of woody debris for population persistence - Maciej Pabijan; Sara Bąk-Kopaniarz; Maciej Bonk; Stanisław Bury; Wioleta Oleś; Weronika Antoł; Izabela Dyczko; Bartłomiej Zając (Ecological Indicators, 2023)
Achieving an understanding of species’ temporal and spatial abundance patterns is a prerequisite for proper conservation and management decisions. Little is known of the ecological indicators of census size or biomass of terrestrial amphibian communities and historical estimates of population size are rare. Here we took advantage of abundance and biomass data collected in 1967/1968 for a leaf-litter amphibian community in Niepołomice Forest (NF) in south-central Poland. Using the same technique (removal sampling), we censused the amphibian community of this forest 50 years later (2016/2017), spatially matching a subset of current plots with the historical sampling sites. Averaged over all plots, we revealed at least a fourfold decline in amphibian abundance from 2817 ± 776 individuals/ha in 1967 to 674 ± 508 individuals/ha currently, paralleled by a decline in biomass from roughly 15.5 ± 1.7 to 3.8 ± 3.1 kg/ha. The decline was more striking (over 15-fold) for current plots placed in the same forest division as the historical plots (mean counts of 157 ± 103 individuals/ha corresponding in biomass to 1.0 ± 0.5 kg/ha). We also recorded a change in species composition between surveys, and propose that conversion of aquatic habitat and forest succession have decreased amphibian diversity and abundance in NF. Further, we estimated densities of anuran amphibians in forest plots differing in management regime and local habitat characteristics for contemporary plots (all historical plots were placed in managed forest). We found that unmanaged, old growth forest plots with coarse woody debris on the forest floor held on average twice as many anurans compared to plots in managed stands. Average body condition of the most common species, Rana temporaria, measured as a scaled mass index, was enhanced in plots situated in old growth forest. Our findings suggest that the preservation of old growth forests containing coarse woody debris may boost anuran abundance, biomass and body condition, and has the potential to buffer against long-term demographic decline. Moreover, the retention of deadwood could be a means of increasing the conservation potential of managed forests for terrestrial amphibian communities.